Achieving excellent superelasticity and extraordinary elastocaloric effect in a directionally solidified Co-V-Ga alloy. (November 2021) - Niu, Yurong; Chen, Haiyang; Zhang, Xiangyu; Li, Shengwei; Cong, Daoyong; Ma, Tianyu; Li, Shilei; Lin, Junpin; Wang, Yan-Dong
Abstract: We demonstrate excellent superelasticity and giant elastocaloric effect in a directionally solidified Co50.7 V33.3 Ga16 alloy. Owing to the formation of [001]A preferentially oriented columnar grains, the as-grown alloy displays nearly perfect superelastic behaviors with fully reversible compressive strain of up to 5.4%, narrow stress hysteresis of about 40 MPa and a wide operating temperature window from 258 to 373 K. Simultaneously, a giant adiabatic temperature change ΔTad of -18.7 K is obtained on removing a uniaxial stress of 400 MPa at room temperature, which is in good agreement with the theoretical values based on Maxwell relation (-19.0 K) and calorimetric measurements (-19.9 K). A large |ΔTad | of greater than 12.5 K is obtained over a wide temperature span of at least 115 K. Moreover, both superelasticity and elastocaloric effect remain good functional stability without any evident degradation for 100 cycles. Graphical abstract: Image, graphical abstract